2011
DOI: 10.1016/j.rfe.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A search for long‐range dependence and chaotic structure in Indian stock market

Abstract: This study tests for the presence of nonlinear dependence and deterministic chaos in the rate of returns series for six Indian stock market indices. The overall result of our analysis suggests that the returns series do not follow a random walk process. Rather it appears that the daily increments in stock returns are serially correlated and the estimated Hurst exponents are indicative of marginal persistence in equity returns. Result from the test of independence on filtered residuals suggests that the existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Rege and Martín (2011) calculated the Hurst exponent for the Portuguese stock market and concluded that it exhibits both long memory and short memory depending on the scale of the time period used. Mishra et al (2011) used R/S analysis on daily returns from the Indian stock market to reveal strong evidence of persistence or temporal dependencies. Mukherjee et al (2011) found no evidence for long memory in the Indian stock market.…”
Section: Long Memorymentioning
confidence: 99%
“…Rege and Martín (2011) calculated the Hurst exponent for the Portuguese stock market and concluded that it exhibits both long memory and short memory depending on the scale of the time period used. Mishra et al (2011) used R/S analysis on daily returns from the Indian stock market to reveal strong evidence of persistence or temporal dependencies. Mukherjee et al (2011) found no evidence for long memory in the Indian stock market.…”
Section: Long Memorymentioning
confidence: 99%
“…The statistical approach is restricted in determining the underlying dynamics of the assets' price evolution. Some recent studies show the presence of nonlinear dependence and deterministic chaos in the real-world financial time series [23,30]. This leads to the increasing interest in an alternative approach when high-frequency financial time series are obtained from the chaotic finance systems [16,21].…”
Section: Introductionmentioning
confidence: 99%
“…providing weak evidences that stock price series behave similar to a chaotic process and the existence of long term dependences can be confirmed within stock price series [8,22,40,42]. However, the existing statistical tests cannot accurately infer whether a series is indeed chaotic or random.…”
Section: Empirical Analysismentioning
confidence: 99%